Venom immunotherapy: A real-life experience in a tertiary referral center in Turkey - Ediger, Dane; Erbay, Muge; Seker, Ummuhan; Esra Gunaydin, Fatma (Annals of Medical Research, 2021)
Aim: Venom allergy is an important health problem because of life-threatening reactions and impaired quality of life. The only treatment that can prevent the risk of a subsequent systemic sting reaction is venom immunotherapy. Additionally, there has been limited report about Hymenoptera venom immunotherapy practice from Turkey. In our clinic, which is an important allergy center in Turkey, we aim to share the clinical characteristics of venom immunotherapy patients and to raise awareness by sharing our experience about venom immunotherapy.Materials and Methods: Between December 2012 and February 2019, adult patients who underwent venom immunotherapy in Uludag University Faculty of Medicine, Department of Immunology and Allergic Diseases outpatient clinic were evaluated. The sociodemographic characteristics of the patients, re-stings and reaction type during venom immunotherapy were recorded. Results: A total of 52 patients (44.2% female, 55.8% men; mean age= 48.4 ± 12.9 years) were included. From a total of 52 patients, 41 (78.8%) received VIT with honey bee, 8 (15.4%) with wasp and 3 (5.8%) with honey bee and wasp. Only 4 (7.7%) patients developed systemic reactions due to venom immunotherapy. During the venom immunotherapy period, 19 (36.5%) patients were re-stung by the culprit bee and none of them had any systemic allergic reactions.Conclusions: Our data is consistent with previous literature regarding safety and effectivenes of venom immunotherapy. We believe that any effort increasing knowledge of venom allergy is important.
Keywords: Hymenoptera; immunotherapy; venom allergy